TALAK DAN ‘IDDAH MENURUT FIQH DAN KOMPILASI HUKUM ISLAM (KHI) - Ratno Asep Sujana; Hani Sholihah (Institut Nahdlatul Ulama Tasikmalaya, 2022)
A happy family physically and mentally is the dream of every couple and individuals in a family. However, it is possible for the coveted goal, the contract they made together was shaken which had an impact on the creation of husband and wife disputes, which ended in divorce (talak). This paper aims to describe various problems related to divorce and iddah in the perspective of fiqh and the Compilation of Islamic Law. The research method used is library research (literature study). The results showed that there were some differences in the provisions of talaq and iddah between fiqh and the Compilation of Islamic Law. The Compilation of Islamic Law stipulates that divorce is only considered valid if it is pronounced before a court session, while fiqh does not stipulate that. This has implications for the early determination of the iddah period.